Roles for menaquinone and the two trimethylamine oxide (TMAO) reductases in TMAO respiration in Salmonella typhimurium: Mu d(Apr lac) insertion mutations in men and tor. - Kwan, H S (1983)
Three groups of mutants defective in trimethylamine oxide (TMAO) reduction were isolated from Salmonella typhimurium LT2 subjected to transposition mutagenesis with Mu d(Apr lac). Mutants were identified by their acidic reaction on a modified MacConkey-TMAO medium. Group I consisted of pleiotropic chlorate-resistant mutants which were devoid of TMAO reductase activity. None expressed the lac operon. Group II mutants were partially defective in TMAO reductase. Electrophoretic studies revealed that they lacked the inducible TMAO reductase, but retained the constitutive activity. The genotypic designation tor was suggested for these mutants. The tor mutation in one was located between 80 and 83 U on the S. typhimurium chromosome. Expression of the lac operon in these mutants was not affected by air, TMAO, or nitrate. Group III mutants reduced little or no TMAO in vivo, but their extracts retained full capacity to reduce it with methyl viologen. These mutants also failed to produce hydrogen sulfide from thiosulfate and could not grow anaerobically on glycerol-fumarate. Two subgroups were distinguished. Vitamin K5 restored wild-type phenotype in subgroup IIIa only; vitamin K1 restored wild-type phenotype in both IIIa and IIIb isolates. The genotypic designation men (menaquinone) was suggested for group III isolates. The mutation in IIIa mutants was cotransducible with glpT, which corresponds to the menBCD site in Escherichia coli. That in IIIb mutants was cotransducible with glpK, which corresponds to the menA site in E. coli. Expression of the lac operon in IIIa, but not IIIb, mutants was repressed by air. An additional mutant group isolated on the same medium consisted of strains defective in formate hydrogenlyase.